2004
DOI: 10.1210/me.2004-0115
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Membrane Estrogen Receptors Exist and Functions as Dimers

Abstract: A small pool of estrogen receptors (ERalpha and -beta) localize at the plasma membrane and rapidly signal to affect cellular physiology. Although nuclear ERs function mainly as homodimers, it is unknown whether membrane-localized ER exists or functions with similar requirements. We report that the endogenous ER isoforms at the plasma membrane of breast cancer or endothelial cells exist predominantly as homodimers in the presence of 17beta-estradiol (E2). Interestingly, in endothelial cells made from ERalpha /E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
208
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(219 citation statements)
references
References 41 publications
9
208
0
2
Order By: Relevance
“…Razandi et al (1999) showed that identical membrane and nuclear ERa and ERb receptors of 67 and 54 kDa, respectively, could arise from a single ERa or ERb transcript expressed in CHO cells. Endothelial cells (EC) from an ERa/b double-KO lack membrane or nuclear ERa or ERb (Razandi et al, 2004). In contrast, a novel membrane-associated 63 kDa membrane ER-X, which cross reacts with anti-ERa antibodies, including MC20, has also been reported in an ERa-KO mouse (Toran-Allerand et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Razandi et al (1999) showed that identical membrane and nuclear ERa and ERb receptors of 67 and 54 kDa, respectively, could arise from a single ERa or ERb transcript expressed in CHO cells. Endothelial cells (EC) from an ERa/b double-KO lack membrane or nuclear ERa or ERb (Razandi et al, 2004). In contrast, a novel membrane-associated 63 kDa membrane ER-X, which cross reacts with anti-ERa antibodies, including MC20, has also been reported in an ERa-KO mouse (Toran-Allerand et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, the nature of the membrane-bound estrogen receptor has been proposed to resemble ERa (Razandi et al 2004;Acconcia et al 2005), and the identity of the ERb localized to membranes remains controversial (Yang et al 2004(Yang et al , 2006. However, it also appears that there may be other novel estrogen receptors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…These E2-activated responses are thought to be mediated through a membrane-associated population of classical ERs. ERα and ERβ are detectable in membrane fractions of breast cancer cells [46] and by immunohistochemistry (IHC) in breast tumor samples within and outside the nucleus [47]. In ER+ MCF7 cells, E2 increases ERα association with c-Src, Shc, and the IGF-1 receptor, ERα-dependent PI3 kinase activation, and proliferation [48][49][50].…”
Section: Crosstalk With Growth Factors and "Nongenomic" E2 Responsesmentioning
confidence: 99%